Studi Riap Mahoni (Swietenia Macropylla King) Area Kegiatan Rehabilitasi Daerah Aliran Sungai (Das) Desa Lolan Kabupaten Bolaang Mongondow - Makai. M; Walangitan. H. D; R. Kainde (Universitas Sam Ratulangi, 2020)
ABSTRAK The basic principle of sustainable forest management is that forest harvest is the same as the forest increment itself, so increment information is very important. Increment is the increase in diameter, basal area, height, volume or value of a tree or stand over a certain period of time. Mahogany tree (Swietenia Macropylla King) can survive in all types of soil, so this plant is very suitable for planting in the context of land rehabilitation activities. This research was conducted in the Watershed Rehabilitation Area (DAS) in Lolan Village, Bolaang Timur District, Bolaang Mongondow Regency in October - November 2018. This study aims to describe the initial increment of mahogany stands (Sweitenia macrophylla King). The technique of determining tree samples using purposive sampling method by selecting trees whose growth has never been disturbed by either pests or broken due to wind. The variables observed were diameter, height, and volume increments. The results showed that the average height and diameter of mahogany trees in blocks A1 & A7 when the plants were 16 months (1.25 years old) were 3.24 m for height and 0.033 m, respectively. The average height increment was 2.594 m / yr, the mean diameter increment was 0.026 m / yr. Furthermore, the average volume increment is 0.00169 m3 / year. Key words: Riap, land rehabilitation, plantation forest